통합 치위생 실습모형 개발 및 적용에 관한 연구 - 박인숙; 우승희; 최미혜; Park, In-Suk; Woo, Seung-Hee; Choi, Mi-hye (Chiwisaeng gwahakoeji, 2010)
The purpose of this study was to develop an inclusive dental hygiene practice model in an effort to stir up the self-directed learning of learners to boost their problem-solving skills and ability of providing inclusive personal oral health care in a systematic and efficient manner. The subjects in this study were 41 dental hygiene students who were in their second year in C college located in South Jeolla Province as of 2009. An inclusive dental hygiene practice was implemented during a 15-week period of time from August 31 to December 7, 2009, and a self-administered survey was conducted before and after that by using the same questionnaires. Whether there were any differences between before and after the application of the inclusive dental hygiene practice model was checked, and there was improvement in all the learning motivation, self-directed learning capabilities and satisfaction level. Concerning the relationship of academic standing to changes in learning motivation, self-directed learning capabilities and satisfaction level, the inclusive dental hygiene practice model brought more favorable changes to the students in the lower tiers. The inclusive dental hygiene model should be applied to not only practical courses but theoretical ones so that learners could make progress both in theory and practice, and evaluation tools geared toward assessing their academic achievement and practical abilities should be developed. 국민의 구강건강을 효율적으로 관리할 수 있는 치과위생사의 역량강화를 위하여 학습자의 자기주도적 학습을 통한 학습자의 문제 해결력을 향상시키기 위한 목적으로 실시한 본 연구는 2009학년도 2학년 41명을 대상으로 2009년 8월 31일부터 2009년 12월 7일까지 15주 동안 기존 실습 교과목의 문제점을 분석하여 이를 개선하기 위한 통합치위생실습모형을 개발하여 적용시켜 치위생실습을 진행하였고 다음과 같은 결론을 도출하였다. 1. 통합 치위생 실습 모형 적용 전 후를 비교분석한 결과 학습동기, 자기주도적 학습력, 만족 도 전반적인 과정 모두 적용 전보다 적용 후 높은 것으로 조사되었다. 특히 학습동기에서는 학습동기의 관련성, 만족감에서 유의한 차이가 있는 것으로 나타났고(p<0.001), 자기주도적 학습력에서는 학습자로서의 자기 확신, 학습에 대한 호기심, 학습에 대한 책임수용에서 유의 한 차이가 있는 것으로 나타났으며(p<0.01), 만족감에서는 학습 전보다 학습 후가 만족감이 큰 것으로 나타났다(p<0.001). 2. 학업수준에 따른 학습동기의 변화와 자기주도학습력의 변화, 수업만족도의 변화를 알아본 결 과, 통합치위생실습 모형이 하위집단 학생들을 긍정적으로 변화시키는데 효과적인 것으로 나 타났다. 3. 통합치위생실습을 통해 기존 단편적인 실습 교육에서 벗어나 실제 환자를 대상으로 예방구 강관리를 시행하는 실물 위주의 교육과 실천학습을 통해 학습자는 자신감을 회복을 비롯한 학업성취도를 높이는 등 긍정적 결과를 보였다. 본 연구 결과를 토대로 학습자의 개인구강관리능력 향상을 위한 학습효과 개선을 위해서는 통합 치위생 실습모형을 실기 교과목에만 한정할 것이 아니라 이론 교과에도 적용하여 이론과 실기 교과목이 연계되어 포괄적인 구강관리 능력을 함양시켜야 하고, 국가고시 합격률 결과만을 위해 주입식 교육만을 행할 수밖에 없는 여건만을 고집할 것이 아니라 학습자 참여를 유도할 수 있는 새로운 교수 학습법을 개발하고 적용해야 할 것으로 사료된다.